HIV/AIDS as a development issue - Barrett, Hazel R.; Digby, Bob (TSG - Top spec geography, 2012)
It is estimated that 60 million people have been infected with HIV since the disease was first identified in the 1980s. UNAID S believe that about 25 million of these have died from AIDS. In 2010, two thirds of the world’s cases of HIV and deaths from AID S occurred in countries in sub-Saharan Africa, while in the USA, Europe and Australia drug treatments now enable those infected with HIV to live with the disease for many decades. This book investigates the global HIV/AIDS pandemic, looking at it specifically as a development issue, with its effects on local and worldwide demographics, and also its role in contemporary problems such as food security. It considers the issues surrounding the disease – including treatments available, prevention strategies, and private and government interventions – at a range of scales. It also looks to the future, and how the pandemic can be tackled given current issues such as the credit crunch, people trafficking and global migration.